Preliminary Results of a Combined Score Based on sIL2-Rα and TIM-3 Levels Assayed Early After Hematopoietic Transplantation - Leotta, Salvatore; Sapienza, Giuseppe; Camuglia, Maria Grazia; Avola, Giuseppe; Marco, Annalia Di; Moschetti, Gaetano; Curto Pelle, Angelo; Markovic, Uros; Milone, Giulio Antonio; Cupri, Alessandra; Bianco, Oriana; Frontini, Viviana; et al. (Frontiers in Immunology, 2020)
Assays of cytokines in plasma at the onset of graft-versus-host disease (GVHD) can predict disease severity and transplant-related mortality (TRM); however, the optimal time to test cytokines, and which panel of cytokines has the highest predictive ability, are unknown. We chose a pre-defined time-point, 18 days after hematopoietic stem cell transplantation (HSCT), to measured plasma levels of six cytokines: soluble interleukin-2 receptor alpha (sIL2-Rα), T-cell immunoglobulin domain and mucin domain-3 (TIM-3), suppression of tumorigenicity-2 (ST-2), intercellular adhesion molecule (ICAM), interferon (IFN)-gamma, and interleukin-6 (IL-6). The study included 95 patients who underwent allogeneic hematopoietic transplantation in our institution between May 2013 and January 2017. Plasma-levels of sIL2-Rα and TIM-3, measured as continuous data, had predictive value for overall survival (sIL2-Rα, p = 0.002; TIM-3, p = 0.0007), while TRM could be predicted by sIL2-Rα (p = 0.0005), IFN gamma (p = 0.01), and IL-6 (p = 0.0001). No cytokine was associated with risk of relapse. Patients were categorized into groups according to cytokine thresholds determined by receiver operating characteristic curve analysis (sIL2-Rα ≤ or > 8100 pg/ml; TIM-3 ≤ or > 950 pg/ml) and multivariate analysis conducted. High levels of both TIM-3 and sIL2-Rα were significant predictors of poor survival (TIM-3 > 950 pg/ml: hazard ratio (HR) = 5.198, p = 0.005 and sIL2-Rα > 8.100 pg/ml: HR = 3.199, p = 0.0007). Using these cut-off thresholds, we constructed a composite scoring system that could distinguish three different groups of patients with varying rates of TRM: high-risk, 41.7%; intermediate risk, 10.8%; and low risk 7.1% (Gray test: p=0.0002). If confirmed in a validation cohort, this composite scoring system could be used to guide modulation of post-transplant immune suppressive therapy.